Development of employment indicators to advance the quality of spinal cord injury rehabilitation care: SCI-High Project. (30th September 2021) - Alavinia, Seyed Mohammad; Jetha, Arif; Hitzig, Sander L.; McCauley, Diana; Routhier, François; Noonan, Vanessa K.; Linassi, Gary; Farahani, Farnoosh; Omidvar, Maryam; Jeyathevan, Gaya; Craven, B. Catharine
Abstract : Context: Employment and Return to Work (RTW) rates following spinal cord injury/disease (SCI/D) are low due to individual and impairments characteristics, secondary health conditions, social and environmental barriers, prior work experience, workplace supports and resources, and physical or psychosocial work demands. To improve RTW, the SCI-High Project team developed a set of Employment structure, process, and outcome indicators for adults with SCI/D in the first 18 months after rehabilitation admission. Methods: A pan-Canadian Working Group of diverse stakeholders: (1) defined the Employment construct; (2) conducted a systematic search of available outcomes measures; (3) constructed a Driver diagram summarizing factors associated with employment. Subsequent facilitated meetings allowed for the creation of structure and process indicators, and the selection of outcome indicators. Results: The structure indicator is the proportion of SCI/D rehabilitation programs with an employment resource center. The process indicator is the proportion of SCI/D rehabilitation inpatients who receive an employment assessment during inpatient rehabilitation. The intermediary and final outcome measures are the Readiness for Return-to-Work Scale (RRTW) and Work Productivity and Activity Impairment (WPAI). Scale A of the RRTW for those who are unemployed and Scale B of RRTW and WPAI will be used for those who are employed. Conclusion: This framework of Employment indicators intends to support the RTW needs of persons with SCI/D by ensuring that rehabilitation professionals provide opportunities to explore RTW within the first 18 months after rehab admission. Increased employment rates have the potential to enhance the wellbeing, health, and longevity of individuals with SCI/D.